2021
DOI: 10.3390/plants10050998
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Resistance to Common Bacterial Blight and Charcoal Rot Disease for the Production of Mesoamerican Common Beans in the Southern United States

Abstract: The gene pool of Mesoamerican common beans (Phaseolus vulgaris L.) includes genotypes in the small-to-medium-size seeded dry beans, as well as some snap beans from hotter environments adapted to the Southeastern United States. However, the warm and humid climate of the Southeastern United States is conducive to diseases such as Common Bacterial Blight (CBB) and Charcoal Rot (CR). The pathogens for these two diseases can survive long periods in infested soil or on seeds and are difficult to control through pest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 83 publications
(130 reference statements)
0
8
0
Order By: Relevance
“…Zhu et al (2016) revealed two markers, BMp10s174 and BMp10s244, on Pv10 (39,730,677 and 40,002,585 bp in G19833). Ambachew et al (2021) found SNPs with minor effects associated with common bacterial blight resistance on Pv02 (8,541,089 bp), Pv04 (29,756,136 bp),Pv08 (24,383,486;55,730,740;55,730,740;8,738,278 bp),Pv10 (1,437,174 bp),and Pv11 (25,981,923 bp). Among them, Pv08 and Pv10 concentrated most of the CBB resistance genes.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Zhu et al (2016) revealed two markers, BMp10s174 and BMp10s244, on Pv10 (39,730,677 and 40,002,585 bp in G19833). Ambachew et al (2021) found SNPs with minor effects associated with common bacterial blight resistance on Pv02 (8,541,089 bp), Pv04 (29,756,136 bp),Pv08 (24,383,486;55,730,740;55,730,740;8,738,278 bp),Pv10 (1,437,174 bp),and Pv11 (25,981,923 bp). Among them, Pv08 and Pv10 concentrated most of the CBB resistance genes.…”
Section: Resultsmentioning
confidence: 95%
“…Wu et al (2017) explored the association mapping of NBS-LRR (nucleotide binding site-leucine CCF Barbosa et al rich repeat) microsatellites and seven of them also mapped by Shi et al (2011). Ambachew et al (2021) detected 14 significant SNPs connected to CBB and over Pv02, Pv04, Pv08, Pv10, and Pv11. Simons et al (2021) identified 8 regions, including 6 previously mapped and two new loci (Pv11 and Pv10).…”
Section: Introductionmentioning
confidence: 99%
“…However, common bean BL and cultivars with enhanced levels of resistance are not yet available. One of the reasons may be because the breeding against ASB has been focused only on Middle American beans that possess tolerance to heat and drought ( Urrea et al., 2009 ; Beebe et al., 2013 ; Ambachew et al., 2021 ) and the severity of M. phaseolina increases in these environments ( Frahm et al., 2004 ; Mayek et al., 2002 ). In fact, BAT 477 and Negro Tacaná were used as donor parents to improve the resistance to M. phaseolina and tolerance to the aforementioned abiotic stresses in the SEA 5 and TARS-MST1 BL, respectively ( Singh et al., 2001 ; Porch et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ashy stem blight (ASB) caused by the fungus Macrophomina phaseolina (Tassi) Goidanich is an important disease in the common bean ( Phaseolus vulgaris L.) in tropical and subtropical regions in the Americas and elsewhere ( Singh and Schwartz, 2010 ; Ambachew et al., 2021 ). This plant pathogen affects roots and all aerial plant parts causing damping off, root rots, stem blight, leaf burning, and premature senescence symptoms ( Islam et al., 2012 ; Kaur et al., 2012 ; Marquez et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ashy stem blight (ASB) is a common disease in the common bean ( Phaseolus vulgaris L.) in tropical and subtropical regions in the Americas and worldwide ( Kaur et al, 2012 ; Ambachew et al., 2021 ). The disease is caused by the seed-transmitted fungus Macrophomina phaseolina (Tassi) Goidanich, and the pathogen can infect the roots and all aerial plant parts during the entire cropping season ( Islam et al., 2012 ; Kaur et al., 2012 ; Viteri and Linares, 2022a ).…”
Section: Introductionmentioning
confidence: 99%